Personal Characteristics and Performance: Mediating Role of Self Efficacy - Jermsittiparsert , Kittisak; Wongsurawat, Kovit (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
The study was planned to examine the direct impact of personal characteristics namely achievement motivating, goal settings, and experience on performance of SMEs in Thailand. In addition to that the study has also examined the direct impact of self-efficacy on the SME performance. Finally, the study has examined the mediating role of self-efficacy in the relationship between the personal characteristics and SME performance. The theoretical frameworks that were developed in various prior studies and the need for achievement theory offer theoretical foundation for this study, and thus confirm that achievement motivation is one of the essential elements for the entrepreneurs. Partial Least Square Structural Equation Modeling (PLS-SEM) was employed and for that purpose we used the Smart PLS 3.0. The results obtained from the analysis were in line with the need for achievement theory. It indicates that individual level performance is positively influenced by achievement motivation due to the positive relationship that exists between organizational performance and achievement motivation. At individual level, the goal setting theory also supports this relationship. The goal setting theory provides a theoretical foundation for these findings i.e. effects of goals setting on performance. Article history : Received 14 April 2021 Revised 11 May 2021 Accepted 12 May 2021 SIMILARITY INDEX = 0.00 %